PENGARUH GAYA KEPEMIMPINAN DAN MOTIVASI SPIRITUAL TERHADAP KINERJA KARYAWAN (STUDI KASUS PADA BADAN KEPEGAWAIAN DAN PENGEMBANGAN SUMBER DAYA MANUSIA KOTA BATU ) - Rifky Nur Fadilla; Abdul Kodir Djaelani; M. Khoirul ABS (E-JRM : Elektronik Jurnal Riset Manajemen, 2019)
ABSTRACT This study aims to describe and analyze the influence of Leadership Style and Spiritual Motivation on the Performance of BKPSDM in Batu City. The type of research used is experimental. The data used are primary and secondary data obtained from questionnaires and interviews. This study amounted to 51 employees who were active employees who were in BKPSDM Batu City. The method used in this research is quantitative descriptive method that is by using analytical tools such as validity, reliability, normality, multicollinearity test, heterocedasticity test, multiple linear analysis test, f test and t test. The results of this study indicate that: (1) the simultaneous influence between the variables of Leadership Style and Spiritual Motivation has an effect on the performance of BKPSDM Kota Batu employees. (2) Leadership Style partially has a significant effect on employee performance and Spiritual Motivation partially has a significant effect on employee performance. Keywords: Leadership Style, Spiritual Motivation and Employee Performance